Method for preparing a compound containing an elastomer and a filler
By mixing wet filler with liquid main batch and controlling mixing conditions, the problem of poor dispersion of filler in rubber is solved, and the mechanical strength and performance consistency of rubber products is improved.
Patent Information
- Application Number
- JP2023534661
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-09
- Filing Date
- 2021-12-08
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2041-12-08
AI Technical Summary
The prior art is difficult to effectively mix various fillers into solid rubber, resulting in poor dispersion quality of fillers in rubber, affecting the mechanical strength and performance consistency of rubber products.
The method of mixing wet filler (containing filler and liquid) with liquid main batch is used to increase the mixing time by controlling parameters such as mixer temperature and rotation speed, and remove part of the liquid by evaporation, thereby improving the dispersion of the filler.
It achieves better dispersion of fillers in rubber, improves the mechanical strength and performance consistency of rubber products, and reduces the interaction and interference between fillers and rubber.
Smart Images

Figure 0007649858000001 
Figure 0007649858000002 
Figure 0007649858000003
Abstract
Description
[Technical field]
[0001] Disclosed herein is a method for making composites from liquid masterbatches and wet fillers and the resulting vulcanizates. [Background technology]
[0002] In the rubber industry there is a constant demand to develop methods for dispersing fillers into elastomers, and it is particularly desirable to develop methods that can do so with respect to the quality, time, effort and / or cost of filler dispersion.
[0003] Many commercially important products are formed as elastomer composites in which reinforcing fillers are dispersed in either various synthetic elastomers, natural elastomers, or elastomer blends. Carbon black and silica, for example, are widely used to reinforce natural rubber and other elastomers. It is customary to produce masterbatches, which are premixes of reinforcing fillers, elastomers, and various optional additives, such as extender oils. Such masterbatches are then compounded with process and curing additives to produce, upon curing, a number of commercially important products. Such products include, for example, pneumatic and non-pneumatic or solid tires for vehicles, including tread portions including caps and bases, undertreads, inner liners, sidewalls, wire skims, carcasses, and the like. Other products include, for example, engine mounts, conveyor belts, windshield wipers, rubber parts for aerospace and marine equipment, vehicle tread elements, seals, liners, gaskets, wheels, bumpers, anti-vibration systems, and the like.
[0004] Good dispersion of reinforcing fillers in rubber compounds is understood to be a factor in obtaining mechanical strength and consistent elastomer composite and rubber compound performance. Considerable effort has been directed to developing methods to improve dispersion quality, and various solutions have been offered to solve this problem. For example, more intensive mixing improves the dispersion of reinforcing fillers, but can degrade the elastomer in which the filler is being dispersed. This is particularly problematic in the case of natural rubber, which is susceptible to mechanical / thermal degradation, especially under dry mixing conditions. Summary of the Invention [Problem to be solved by the invention]
[0005] Thus, a need exists to develop new methods for incorporating various fillers into solid elastomers to obtain acceptable and / or enhanced dispersion qualities and functionality of the elastomer composites, which translate into acceptable or enhanced properties of the corresponding vulcanized rubber compounds and rubber articles. [Means for solving the problem]
[0006] Disclosed herein is a method for preparing a composite material. In one embodiment, the method comprises: (a) charging a mixer having one or more rotors with (i) at least one liquid masterbatch comprising a first filler dispersed in at least one elastomer, and (ii) a wet filler comprising a second filler and a liquid present in an amount ranging from 15% to 65% by weight based on the total weight of the wet filler; (b) mixing the liquid masterbatch with a wet filler in one or more mixing steps, wherein in at least one of said mixing steps, said mixing step is conducted at a mixer temperature controlled by at least one temperature control means, and at least a portion of the liquid is removed from the mixture by evaporation; and (c) discharging from the mixer a composite comprising first and second fillers dispersed in at least one elastomer at a total loading of at least 20 phr, the composite having a liquid content of 10% by weight or less, based on the total weight of the composite; Contains:
[0007] With respect to any aspect or method or embodiment disclosed herein, if applicable, the method may further include one or more of the following aspects; in step (b) and optionally in step (a), the at least one temperature control means is set to a temperature Tz of 65°C or higher, e.g., a TCU temperature in the range of 65°C to 100°C, and the composite discharged in step (c) is free of one or more rubber chemicals and the wetting filler has a liquid present in an amount in the range of 30% to 65% by weight.
[0008] For any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following aspects: the at least one elastomer is selected from the group consisting of natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, functionalized polybutadiene rubber, polyisoprene rubber, ethylene-propylene rubber, isobutylene based elastomers, polychloroprene rubber, nitrile rubber, hydrogenated nitrile rubber, and polysulfide rubber. the solid elastomer is selected from natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, functionalized polybutadiene rubber, and mixtures thereof, and the charging step further comprises charging the mixer with at least one additional elastomer, the at least one additional elastomer being different from the at least one elastomer of the liquid masterbatch to form a composite comprising the elastomer mixture, the at least one elastomer of the liquid masterbatch being natural rubber, and the at least one additional elastomer being selected from polybutadiene and styrene-butadiene rubber.
[0009] For any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following aspects: the filler comprises at least one material selected from carbonaceous materials, carbon black, silica, nanocellulose, lignin, clay, nanoclay, metal oxides, metal carbonates, pyrolytic carbon, regenerated carbon, graphene, graphene oxide, reduced graphene oxide, carbon nanotubes, combinations thereof, and coated and treated materials thereof; the filler comprises at least one material selected from carbon black, silica, and silicon-treated carbon black; the filler comprises carbon black; the wet filler comprises undried carbon black; the wet filler comprises rewetted dried carbon black; the filler comprises silica; the wet filler comprises undried silica, where the filler comprises silica; and the method further includes charging the mixer with a crosslinker. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Disclosed herein is a method for preparing or forming a composite by mixing a liquid masterbatch with a wet filler.
[0011] When mixing fillers and elastomers, the challenge is to ensure that the mixing time is long enough to ensure sufficient filler dispersion before the elastomer in the mixture experiences high temperatures and begins to degrade. In the methods disclosed herein, the use of a wetting filler (e.g., including a filler and a liquid) allows batch times and temperatures to be controlled beyond those achievable with known dry mixing processes and can provide other benefits, such as enhanced filler dispersion and / or promotion of rubber-filler interaction and / or improved rubber compound performance. It can be effective if sufficient liquid is used to wet a substantial portion or substantially all of the filler surface prior to mixing with the liquid masterbatch. Typically, and as described herein, the mixing process can be accomplished by controlling one or more mixer or process parameters, such as the mixer surface temperature and / or rotor speed, the fill rate, mixing of rubber chemicals (if any) at later times in the mixing cycle, the composite discharge temperature, and / or the application of two or more mixing stages.
[0012] The composite formed by the method disclosed herein is considered to be an uncured mixture of filler and elastomer, optionally with one or more additives, which will be discussed in more detail herein. The composite formed can be considered a mixture or masterbatch. The composite formed can optionally be an intermediate product that can be used in subsequent rubber compounding and one or more vulcanization processes. The composite prior to compounding and vulcanization can also be subjected to further processes, such as one or more holding steps or further mixing steps, one or more further drying steps, one or more extrusion steps, one or more calendaring steps, one or more grinding steps, one or more granulation steps, one or more baling steps, one or more twin-screw exhaust extrusion steps, or one or more rubber processing steps, to obtain a rubber compound or rubber article.
[0013] The method of preparing the composite comprises the steps of charging or introducing into a mixer at least a liquid masterbatch and a wetting filler, e.g., a) one or more liquid masterbatches and b) one or more wetting fillers, where at least one filler or a portion of at least one filler is wetted with a liquid while being mixed with the liquid masterbatch. The liquid masterbatch is mixed with the wetting filler to form a mixture during the mixing step. The method includes a mixing step in which at least a portion of the liquid is removed by evaporation in one or more mixing steps, or an evaporation process that occurs during mixing. The liquid of the wetting filler can be removed by evaporation (and at least a portion can be removed under the claimed mixing conditions) and can be a volatile liquid, e.g., volatile at the bulk mixture temperature. For example, the liquid may have a boiling point of 180° C. or less at 1 atm, e.g., 170° C. or less, 160° C. or less, 150° C. or less, 140° C. or less, 130° C. or less, 120° C. or less, 110° C. or less, or 105° C. or less, e.g., 60° C. to 180° C., 60° C. to 170° C., 60° C. to 160° C., 60° C. to 150° C., 60° C. to 140° C., 60° C. to 15 ... The liquid may have a boiling point of 130° C., 60° C. to 120° C., 60° C. to 110° C., 60° C. to 100° C., 60° C. to 90° C., 90° C. to 180° C., 90° C. to 170° C., 90° C. to 160° C., 90° C. to 150° C., 90° C. to 140° C., 90° C. to 130° C., 90° C. to 120° C., 90° C. to 110° C., 90° C. to 100° C., 95° C. to 120° C., or 95° C. to 110° C. For example, a volatile liquid may be distinguished from an oil (e.g., an extender oil), which may be present during at least a portion of the mixing process, and thus the oil is meant to be present in the discharged composite, and thus does not evaporate during a substantial portion of the mixing time.
[0014] As used herein, "liquid masterbatch" refers to a masterbatch derived from an elastomer latex or polymer solution and a filler slurry (e.g., carbon black or silica slurry) fed into a liquid mixing system, such as an agitated tank. Such "liquid masterbatch" technology can be used with natural rubber latex and emulsified synthetic elastomers, such as styrene butadiene rubber (SBR), or other elastomeric polymers in liquid form. Continuous or semi-continuous techniques for producing liquid masterbatches, such as those disclosed in U.S. Patent Nos. 6,048,923 and 8,586,651, the contents of which are incorporated herein by reference, are effective for producing liquid masterbatch composites characterized by high quality.
[0015] With respect to the liquid masterbatch used in any of the methods disclosed herein, the masterbatch is in solid form during the filling step and subsequent mixing step with the wet filler. The liquid masterbatch may comprise a dehydrated and / or dried product of the liquid masterbatch process. Thus, the liquid masterbatch comprises at least one elastomer and at least one filler. A liquid masterbatch for purposes of the present invention has a water content (or moisture content) of 5% by weight or less, 4% by weight or less, 3% by weight or less, 2% by weight or less, 1% by weight or less, or 0.1% to 5% by weight, 0.5% to 5% by weight, 1% by weight to 5% by weight, 0.5% to 4% by weight, etc.
[0016] The liquid masterbatch (e.g., starting masterbatch) includes an elastomer with at least one filler and, optionally, other ingredients. For example, the liquid masterbatch can include, on a dry weight basis, 10 phr to 100 phr of filler predispersed in the elastomer, or 20 phr to 100 phr, 20 phr to 80 phr, 30 phr to 70 phr, or 40 phr to 60 phr of filler predispersed in the elastomer, etc. The other ingredients can be present in an amount of 0.1 phr to less than 50 phr.
[0017] The liquid masterbatch can contain any of the elastomers, any of the fillers, any of the additives, and any combinations thereof in any amounts as described and exemplified herein and as known in the art, with the total filler present in the final composite including any wet fillers added according to the methods disclosed herein plus any fillers predispersed in the liquid masterbatch.
[0018] A liquid masterbatch can be a composite, mixture or formulation made by a liquid masterbatch process and can be any premixed composite of filler dispersed in an elastomer while the elastomer is in a liquid state, such as a latex, dispersion or solution, or in a wet state, such as an intermediate material from a synthetic or natural rubber manufacturing process. A liquid masterbatch can be any liquid-liquid masterbatch, or other liquid or wet masterbatch process, such as those described in U.S. Patents 6,048,923, 6,929,783 B2, 8,586,651 B2, 10,000,612 B2, 10,000,613 B2, 10,301,439 B2, 10,125,229 B2, 9,758,627 B2, 10,179,843 B2, 10,343,455 B2, 10,439,512 B2, 10,512 ... Nos. 10,106,674, 10,017,612, 10,253,141, 9,834,658, 9,616,712, U.S. Patent Application Publication Nos. 2019 / 002650A1, 2019 / 031836A1, International Publication No. WO2018 / 219631A1, and International Application No. PCT / US20 / 36168, the contents of which are incorporated herein by reference.
[0019] The liquid masterbatch may be or may include natural rubber and / or synthetic elastomers and / or rubbers. Types of elastomers include natural rubber (NR), styrene butadiene rubber (SBR, solution SBR (SSBR), emulsion SBR (ESBR), oil extended SSBR (OESSBR) etc.), polybutadiene (BR) and polyisoprene rubber (IR), ethylene-propylene rubber (EPDM etc.), isobutylene based elastomers (butyl rubber etc.), polychloroprene rubber (CR), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), polysulfide rubber, polyacrylate elastomers, fluoroelastomers, perfluoroelastomers, and silicone elastomers.
[0020] Exemplary elastomers include natural rubber, SBR, BR, IR, functionalized SBR, functionalized BR, functionalized NR, EPDM, butyl rubber, halogenated butyl rubber, CR, NBR, HNBR, fluoroelastomers, perfluoroelastomers, and silicone rubbers, such as natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, functionalized polybutadiene rubber, polyisoprene rubber, ethylene-propylene rubber, nitrile rubber, hydrogenated nitrile rubber, hydrogenated SBR, and mixtures thereof. Mixtures of two or more types of elastomers can be formed, including blends of synthetic and natural rubber, or with two or more types of synthetic or natural rubber. Other synthetic polymers that can be used in the present method (either alone or as a mixture) include hydrogenated SBR, and thermoplastic block copolymers (e.g., recyclable, etc.). Synthetic polymers include copolymers of ethylene, propylene, styrene, butadiene, and isoprene. Other synthetic elastomers include those synthesized by metallocene chemistry, where the metal is selected from Ce, Pr, Nd, Sm, Gd, Tb, Dy, Ho, Tm, Yb, Lu, Co, Ni, and Ti. Polymers made from bio-based monomers can also be used, such as monomers containing modern carbon as defined by ASTM D6866, such as bio-based styrene monomers as disclosed in U.S. Pat. No. 9,868,853, the disclosure of which is incorporated herein by reference, or polymers made from bio-based monomers such as butadiene, isoprene, ethylene, propylene, farnesene, and comonomers thereof. For example, a mixture can be formed by mixing one or more elastomers (such as a "further" or "second" elastomer) with at least one liquid masterbatch, and the resulting mixture is then charged into a mixer with a wet filler.Alternatively, the additional elastomer can be charged into the mixer with the liquid masterbatch and the wet filler subsequently mixed in. As an alternative, the additional elastomer can be charged into the mixer separately or as an elastomer premix.
[0021] Alternatively and / or in addition, the composite discharged after mixing the liquid masterbatch with the wet filler (and optionally further elastomer) can be further mixed with one or more elastomers or further masterbatches. The further masterbatch can be a liquid masterbatch, a masterbatch formed by mixing a solid elastomer with a filler (wet or dry filler, such as silica, carbon black, silicon-treated carbon black, and / or any filler disclosed herein), a wet masterbatch, such as an intermediate material from a synthetic or natural rubber manufacturing process or a composite manufacturing process, having a water (or moisture or aqueous fluid content) of 25% by weight based on the total weight of the wet liquid masterbatch, or a mixture thereof.
[0022] For example, the further masterbatch can be a liquid masterbatch formed from a solvent masterbatch process. For example, the silica / elastomer masterbatch can be prepared as described in U.S. Pat. Nos. 9,758,627 and 10,125,229, or can be a masterbatch from neodymium-catalyzed polybutadiene as described in U.S. Pat. No. 9,758,646, the disclosures of which are incorporated herein by reference. The masterbatch can be a fibrous filler, such as poly(p-phenylene terephthalamide) pulp as described in U.S. Pat. No. 6,068,922, the disclosures of which are incorporated herein by reference. Other masterbatches include those described in International Publication WO 2020 / 247663, the disclosures of which are incorporated herein by reference. For example, the masterbatch can have a filler, such as carbon black, and / or silica, and butadiene rubber. The further masterbatch can be a commercially available masterbatch, such as Emulsil™ silica / SBR masterbatch or Emulblack™ carbon black / SBR masterbatch (both available from the Dynasol group). The further elastomer or further masterbatch can comprise the same elastomer as the liquid masterbatch, or another elastomer selected from one or more elastomers described herein or known in the art, and can further comprise at least one rubber chemical described herein or known in the art.
[0023] Exemplary masterbatches containing elastomer blends include blends of natural rubber and synthetic, bio-based, and / or functionalized elastomers (e.g., SSBR, ESBR, BR), where the filler can be selected from one or more of carbon black, silica, and silicon-treated carbon black.
[0024] The liquid masterbatch can be or contain natural rubber. The natural rubber can also be chemically modified in any way. For example, natural rubber can be treated to modify or alter various non-rubber components chemically or enzymatically, or the rubber molecule itself can be modified with various monomers or other chemical groups, such as chlorine. Other examples include epoxidized natural rubber having a nitrogen content of up to 0.3% by weight, as described in PCT Publication WO2017 / 207912.
[0025] Other exemplary elastomers include, but are not limited to, polymers (e.g., homopolymers, copolymers and / or terpolymers) of rubber, 1,3-butadiene, styrene, isoprene, isobutylene, 2,3-dialkyl-1,3-butadiene (wherein the alkyl can be methyl, ethyl, propyl, etc.), acrylonitrile, ethylene, propylene, and the like. The elastomers can have a glass transition temperature in the range of 120°C to 0°C as measured by differential scanning calorimetry (DSC). Examples include, but are not limited to, styrene-butadiene rubber (SBR), natural rubber and its derivatives, such as chlorinated rubber, polybutadiene, polyisoprene, poly(styrene-co-butadiene), and oil-extended derivatives of any of the foregoing. Mixtures of any of the foregoing can also be used. Particularly suitable synthetic rubbers include copolymers of styrene and butadiene containing from about 10% to about 70% by weight styrene and from about 90 to about 30% by weight butadiene, such as a copolymer of 19 parts styrene and 81 parts butadiene, a copolymer of 30 parts styrene and 70 parts butadiene, a copolymer of 43 parts styrene and 57 parts butadiene, and a copolymer of 50 parts styrene and 50 parts butadiene; polymers and copolymers of conjugated dienes, such as polybutadiene, polyisoprene, polychloroprene, and the like, as well as copolymers of such conjugated dienes with ethylene group-containing monomers copolymerizable therewith, such as styrene, methylstyrene, chlorostyrene, acrylonitrile, 2-vinylpyridine, 5-methyl-2-vinylpyridine, 5-ethyl-2-vinylpyridine, 2-methyl-5-vinylpyridine, allyl-substituted acrylates, vinyl ketones, methyl isopropenyl ketone, methyl vinyl ether, alpha-methyl ene carboxylic acids, and esters and amides thereof, such as acrylic acid and dialkyl acrylic acid amides. Also suitable for use herein are copolymers of ethylene and other higher alpha olefins, such as propylene, 1-butene, and 1-pentene.Other polymers are disclosed in U.S. Patent Application Publication No. 2018 / 0282523 and European Patent Application No. 2423253B1, the disclosures of which are incorporated herein by reference, and include silicone-based elastomers or hybrid systems having silicone and hydrocarbon domains.
[0026] The liquid masterbatch can be a single or multiple or agglomerated particulate material. The multiple liquid masterbatches or agglomerated particulate materials can be obtained by cutting or grinding using methods known in the art. The size of the pieces can have a dimension of at least 1 μm, for example at least 10 μm or at least 100 μm, 10 cm or less, 5 cm or less, or 1 cm or less.
[0027] At least the liquid masterbatch and the wet filler are charged (e.g., fed, introduced) into the mixer. Charge can occur in any manner including, but not limited to, conveying, metering, dosing, and / or feeding the liquid masterbatch and wet filler into the mixer in a batch, semi-continuous, or continuous stream.
[0028] As an option for the filling step, the liquid masterbatch can be masticated until it reaches a predetermined temperature, for example, a temperature of about 90°C or 100°C or higher, before the wet filler is charged into the mixer. Alternatively, the liquid masterbatch can be masticated with at least a portion of the wet filler to a temperature of about 90°C or 100°C or higher before the start of any actual mixing. This temperature can be 90°C to 180°C, 100°C to 180°C, 110°C to 170°C, 120°C to 160°C, or 130°C to 160°C. The elastomer can be masticated using an internal mixer, such as a Banbury mixer, an extruder, a roll mill, a continuous compounder, or other rubber mixing equipment.
[0029] As an option, the loading of the wet filler can be such that the dry filler is introduced into the mixer and wetted by adding liquid (either sequentially or simultaneously or nearly simultaneously) to form a wet filler in the mixer, and then the liquid masterbatch can be added to the mixer. The introduction of the wetted dry filler can be done with all or a portion of the intended filler (e.g., one or more additional portions of the wet filler are further added into the mixer to obtain the total intended amount of wet filler).
[0030] As an option, the liquid masterbatch (all or part) or the wetting filler (all or part) can be added separately but within 20 minutes, or within 15 minutes, or within 10 minutes, or within 5 minutes, or within 1 minute of each other, within 30 seconds of each other, or within 15 seconds of each other.
[0031] With respect to mixing, mixing can be performed in one or more mixing steps. By "one or more mixing steps" it is understood that one mixing step is performed or the first mixing step is followed by a further mixing step before discharge. For example, the one or more mixing steps can include a first mixing step, in which the liquid master batch and the wet filler are mixed under conditions where a minimum amount of liquid is removed by evaporation. For example, the first mixing step can form a premix. The mixture from this first mixing step can then be subjected to a second or further mixing step. As understood in the art, a mixing step is the same as a mixing stage.
[0032] As mentioned above, during one or more mixing steps, in any of the methods of the invention, at least some liquid present in the mixture and / or the wet filler introduced is removed at least in part by evaporation. As an option, a majority (in weight percent) of any liquid removed from the mixture occurs by evaporation. For example, based on the total mass of liquid removed during the mixing steps, at least 50% of the liquid is removed by evaporation. The total mass of liquid removed can be determined from the difference between the liquid content of the wet filler and any liquid remaining in the composite when discharged from the mixer plus any liquid present in the mixer that can be discharged as liquid when the composite is discharged from the mixer. For example, when the composite is discharged, additional liquid can also be discharged, either with the composite or through another outlet provided in the mixer. Other examples include removing liquid by evaporation of at least 50%, at least 60%, at least 70%, at least 80%, or 51% to 100%, 51% to 95%, 51% to 90%, 51% to 80%, 51% to 70%, 60% to 100%, 60% to 95%, 60% to 90%, or 60% to 80% by weight of the total liquid contained in the wet filler charged to the mixer.
[0033] As an option, one or more of the mixing steps or stages can further remove a portion of the liquid from the mixture by squeezing, compressing, and / or squeezing, or any combination thereof. Alternatively, a portion of the liquid can be discharged from the mixer after or as the composite is discharged.
[0034] With regard to the mixer that can be used in the process of the present invention, any suitable mixer that can mix (e.g., mix together or compound together) the filler with the liquid masterbatch can be used. The mixer can be a batch mixer or a semi-continuous mixer or a continuous mixer. A combination of mixers and processes can be used in the present invention, and the mixer can be used in a front-to-back sequence and / or in combination with other processing equipment. The mixer can be an internal mixer or a closed mixer or an open mixer, or an extruder or a continuous compounder or a kneading mixer or a combination thereof. The mixer can mix the filler into the liquid masterbatch and / or disperse the filler into the elastomer and / or distribute the filler into the elastomer. Any or a combination of commercial mixers for producing rubber compounds can be used in the process of the present invention.
[0035] The mixer can have one or more rotors (at least one rotor). The at least one rotor or the one or more rotors can be a screw type rotor, an intermeshing rotor, a tangential rotor, a kneading rotor, a rotor used in an extruder, a roll mill that provides a significant overall specific energy, or a creper mill. Typically, one or more rotors are used in a mixer, for example, a mixer can incorporate one rotor (e.g., a screw type rotor), two, four, six, eight, or nine or more rotors. The set of rotors can be arranged in a parallel direction and / or in a sequential direction in a given mixer configuration.
[0036] The one or more mixing steps can be a single mixing step, e.g., one stage, or a single stage mixing step or process. At least one mixer temperature is controlled by a temperature control means. Furthermore, at least one mixer rotor or rotors can be operated at a tip speed of at least 0.6 m / sec for at least 50% of the mixing time, and / or the temperature control means can be set at a temperature of 65°C or higher (TCU temperature). The one or more mixing steps can be batch or continuous mixing. In a particular example, in a single stage or single mixing step, the composite can be discharged with a liquid content of 10% by weight or less. In other embodiments, two or more mixing steps or mixing stages can be performed, so long as one of the mixing steps is performed under one or more of the above conditions.
[0037] The temperature control means can be, but is not limited to, the flow or circulation of a heat transfer fluid through a passage in one or more parts of the mixer. For example, the heat transfer fluid can be water or a heat transfer oil. For example, the heat transfer fluid can flow through the rotor, the mixing chamber walls, the ram, and the drop door. In other embodiments, the heat transfer fluid can flow through a jacket (e.g., a jacket with a fluid flow means) or a coil around one or more parts of the mixer. Alternatively, the temperature control means can be an electrical element embedded in the mixer (e.g., providing heat). The system providing the temperature control means can further include a means for measuring either the temperature of the heat transfer fluid or the temperature of one or more parts of the mixer. The temperature measurements can be provided to a system used to control the heating and cooling of the heat transfer fluid. For example, the desired temperature of at least one surface of the mixer can be controlled by setting the temperature of the heat transfer fluid located in a passage adjacent to one or more parts of the mixer, such as the walls, the door, the rotor, etc.
[0038] The temperature of the at least one temperature control means may be set and maintained by one or more temperature control units ("TCU"). This set temperature, or TCU temperature, is referred to herein as "T z In the case of a temperature control means that includes a heat transfer fluid, T z is a measure of the temperature of the fluid itself.
[0039] In one option, the temperature control means may be set to a temperature between 30°C and 150°C, 40°C and 150°C, 50°C and 150°C, or 60°C and 150°C, e.g., 30°C and 155°C, 30°C and 125°C, 40°C and 125°C, 50°C and 125°C, 60°C and 125°C, 30°C and 110°C, 40°C and 110°C, 50°C and 110°C, 60°C and 110°C, 30°C and 100°C, 40°C and 100°C, 50°C and 100°C, 60°C and 110°C. The temperature, Tz, can be set in the ranges of 30° C. to 100° C., 30° C. to 95° C., 40° C. to 95° C., 50° C. to 95° C., 50° C. to 95° C., 30° C. to 90° C., 40° C. to 90° C., 50° C. to 90° C., 65° C. to 95° C., 60° C. to 90° C., 70° C. to 110° C., 70° C. to 100° C., 70° C. to 95° C., 70° C. to 90° C., 75° C. to 110° C., 75° C. to 100° C., 75° C. to 95° C., or 75° C. to 90° C. Other ranges are possible with equipment available in the art.
[0040] Compared to dry mixing, for the same type of filler, type of elastomer, and type of mixer, the process allows for higher energy input. The controlled removal of water from the mix allows for longer mixing times and thus improves filler dispersion. As described herein, the method provides operating conditions that balance longer mixing times with evaporation or removal of water within a reasonable time.
[0041] Other operating parameters to be considered include the maximum pressure that can be used. The pressure affects the temperature of the filler and rubber mix. If the mixer is a batch mixer equipped with a ram, the pressure inside the mixer chamber can be influenced by controlling the pressure applied to the ram cylinder.
[0042] As disclosed herein, the liquid masterbatch comprises at least one elastomer, with a filler dispersed therein. The filler dispersed in the masterbatch can be the same as or different from the filler of the wet filler, such that the liquid masterbatch comprises a first filler and the wet filler comprises a second filler. The first and second fillers can independently comprise a single filler or a mixture of fillers. For example, the first filler can be a filler mixture, whereas the second filler can be a single filler type, the first filler can be a single filler type and the second filler can be a filler mixture, or the first and second fillers can each be a single filler type or each be a filler mixture.
[0043] In any of the methods disclosed herein, a discharge step from the mixer occurs to provide a composite including fillers dispersed in the natural rubber at a total loading of at least 20 phr, e.g., 20-250 phr, or other loadings described herein, i.e., at least the first and second fillers combined. In one option, the discharge occurs based on a prescribed mixing time. The mixing time between the start of mixing and the discharge can be about 1 minute or more, e.g., about 1 minute to 40 minutes, about 1 minute to 30 minutes, about 1 minute to 20 minutes, or 1 minute to 15 minutes, or 3 minutes to 30 minutes, 5 minutes to 30 minutes, or 5 minutes to 20 minutes, or 5 minutes to 15 minutes, or 1 minute to 12 minutes, or 1 minute to 10 minutes, or other times. Alternatively, in a batch internal mixer, the ram dwell time can be used as a parameter to monitor the batch mixing time, e.g., the time the mixer is operated with the ram at its lowest position, e.g., in a fully locked position or with the ram deflected (as described in PCT Publication WO2020 / 247663, the contents of which are incorporated herein by reference). The ram dwell time can be 30 minutes or less, 15 minutes or less, 10 minutes or less, or in a range of 3 minutes to 30 minutes, or 5 minutes to 15 minutes, or 5 minutes to 10 minutes. As an option, the discharge occurs based on the discharge or discharge temperature. For example, the mixer can have a discharge temperature in the range of 120°C to 190°C, 130°C to 180°C, e.g., 140°C to 180°C, 150°C to 180°C, 130°C to 170°C, 140°C to 170°C, 150°C to 170°C, or other temperatures within or outside those ranges.
[0044] The method further includes discharging the formed composite from the mixer. The discharged composite may have a water content of 10% by weight or less, based on the total weight of the composite, as abbreviated by the formula: Water content of composite, % = 100 x [mass of water] / [mass of water + mass of dry composite]
[0045] In any of the methods disclosed herein, the discharged composite can have a water content of 10% or less, 5% or less (e.g., the filler also contains water), 2% or less, or 1% or less by weight, based on the total weight of the composite, which can range from 0.1% to 10%, 0.1% to 5%, 0.1% to 3%, 0.1% to 2%, 0.5% to 5%, or 0.5% to 5% by weight, based on the total weight of the composite discharged from the mixer at the end of the process.
[0046] In any of the methods disclosed herein, the water content in the composite ("moisture content") can be measured as the mass of water present in the composite, based on the total mass of the composite. Any number of instruments are known in the art for measuring water content in rubber materials, such as coulometric Karl Fischer titration systems, or moisture balances, such as those manufactured by Mettler (Toledo International, Inc., Columbus, Ohio).
[0047] While in any of the methods disclosed herein the discharged composite has a water content of 10% by weight or less, optionally there may be water present in the mixer that is not retained in the discharged composite, this excess water is not part of the composite and is not part of any calculated water content for the composite.
[0048] In any of the methods disclosed herein, the overall water content of the material charged into the mixer is greater than the water content of the composite discharged at the end of the process. For example, the water content of the discharged composite can be 10%-99.9% (wt. % to wt. %), 10%-95%, or 10%-50% less than the liquid content of the material charged into the mixer.
[0049] In some dry mix processes, one or more rubber chemicals (e.g., processing aids) may be loaded early in the mix cycle to aid in the mixing of the filler. However, the rubber chemicals may interfere with the bonding or interaction between the filler and the elastomer surface and may adversely affect crosslink properties. It has been found that the use of a wet filler allows for mixing in the absence, or substantial absence, of such rubber chemicals.
[0050] Thus, as an alternative, any of the methods disclosed herein include charging at least the liquid masterbatch and the wet filler into a mixer, and mixing the liquid masterbatch and the wet filler in one or more mixing steps to form a mixture in the substantial absence of rubber chemicals and at a mixer temperature controlled by at least one temperature control means. Optionally, the process further includes adding at least one additive selected from antidegradants and crosslinkers during the charging or mixing, i.e., during one or more mixing steps. Examples of such antidegradants (e.g., antioxidants) and crosslinkers are described herein. The term "substantial absence" as defined herein refers to a process in which the filling step and one or more mixing steps can be carried out in the presence of one or more rubber chemicals in an amount of less than 10% by weight of the total amount of rubber chemicals ultimately provided in the vulcanizate prepared from the composite, e.g., the cured composite, or the filling step and one or more mixing steps can be carried out in the presence of one or more rubber chemicals in an amount of less than 5% by weight, or less than 1% by weight of the total amount of rubber chemicals in the final composite. Since the inclusion of rubber chemicals in the composite is optional, a suitable indicator for determining the "substantial absence" of one or more rubber chemicals is to determine the targeted amount in the vulcanizate prepared from the composite, e.g., after the composite is cured. Thus, a nominal amount of one or more rubber chemicals can be added during the filling or mixing, but not in an amount sufficient to prevent filler-elastomer interaction. As a further example of "substantial absence," the loading and mixing can be conducted in the presence of one or more rubber chemicals in an amount or loading of 5 phr or less, 4 phr or less, 3 phr or less, 2 phr or less, 1 phr or less, or 0.5 phr or less, 0.2 phr or less, 0.1 phr or less, based on the resulting vulcanizate.
[0051] In any of the embodiments disclosed herein, as an option, after mixing of at least the liquid master batch and the wet filler is initiated and before the discharging step, the method can further include adding at least one antidegradant to the mixer, whereby the at least one antidegradant is mixed with the liquid master batch and the wet filler. The optional addition of the antidegradant can occur any time before the discharging step. For example, the addition of the antidegradant can occur before the composite is formed and has a water content of less than 10%, or less than 5% by weight. Examples of antidegradants that can be introduced can be N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (6PPD) and others described in other sections herein. The antidegradant can be introduced in an amount ranging from 1% to 5%, 0.5% to 2%, or 0% to 3% by weight based on the weight of the composite being formed. Antidegradants added during the filling or mixing process can help prevent degradation during mixing of the elastomer; however, due to the presence of water in the mix, the rate of degradation of the elastomer is slower compared to the dry mix process, and the addition of the antidegradant can be delayed.
[0052] After the composite is formed and discharged, the method can further include the optional step of mixing the composite with an additional elastomer to form a composite comprising a mixture of elastomers. The "additional elastomer" or second elastomer can be additional natural rubber or can be other than natural rubber, such as any one or more synthetic elastomers disclosed herein (e.g., styrene butadiene rubber (SBR), polybutadiene (BR) and polyisoprene rubber (IR), ethylene propylene rubber (e.g., EPDM), isobutylene-based elastomers (e.g., butyl rubber), polychloroprene rubber (CR), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), polysulfide rubber, polyacrylate elastomers, fluoroelastomers, perfluoroelastomers, silicone elastomers). Mixtures of two or more types of elastomers (mixtures of first and second elastomers) can be used as well, including mixtures of synthetic and natural rubbers or mixtures of two or more types of synthetic or natural rubbers.
[0053] In addition to the liquid masterbatch and the wet filler, the mixer can be charged with one or more charges of at least one additional elastomer to form a composite mixture. Alternatively, the process can include mixing the discharged composite with an additional elastomer to form a mixture. The at least one additional elastomer can be the same as the solid elastomer or different from the solid elastomer.
[0054] Alternatively, the composite, when discharged, may contain at least one additive selected from antidegradants and crosslinking agents, which is added at any time during filling or mixing.
[0055] Alternatively, one or more rubber chemicals can be added with the mixer temperature at or above 120°C, at which point the filler has been distributed and mixed into the elastomer and the addition of the rubber chemicals is not expected to interfere with the interaction between the filler and the elastomer.
[0056] In any of the processes disclosed herein, a discharge step from the mixer occurs and results in a composite including the filler (the sum of the first and second fillers) dispersed in the elastomer at a loading of at least 20 phr. For example, the filler loading can range from 20 phr to 250 phr, 20 phr to 200 phr, 20 phr to 180 phr, 20 phr to 150 phr, 20 phr to 100 phr, 20 phr to 90 phr, 20 phr to 80 phr, 30 phr to 200 phr, 30 phr to 180 phr, 30 phr to 150 phr, 30 phr to 100 phr, 30 phr to 80 phr, 30 phr to 70 phr, 40 phr to 200 phr, 40 phr to 180 phr, 40 phr to 150 phr, 40 phr to 100 phr, 40 phr to 80 phr, 35 phr to 65 phr, or 30 phr to 55 phr. Alternatively, other filler loadings are applicable and disclosed herein. Fillers include carbon black, silica, silicon treated carbon black, and other fillers disclosed herein, and mixtures thereof.
[0057] In certain embodiments, at least 50% of the filler (e.g., at least 75% or at least 90% of the filler) is selected from carbon black and its coated and treated materials. In certain embodiments, at least 50% of the filler (e.g., at least 75% or at least 90% of the filler) is silica. In certain embodiments, at least 50% of the filler (e.g., at least 75% or at least 90% of the filler) is silicon-treated carbon black.
[0058] The wet filler used in any of the methods disclosed herein can be a solid material, such as a solid mass material in the form of a powder, paste, pellet, or cake. In the present methods, the wet filler can be dispersed in the elastomer at a loading ranging from 20 phr to 250 phr, 20 phr to 200 phr, such as 20 phr to 180 phr, 20 phr to 150 phr, 20 phr to 120 phr, or 20 phr to 100 phr, as well as other ranges disclosed herein.
[0059] In any of the methods disclosed herein, the wet filler, e.g., wet carbon black, wet silica, or wet silicon-treated carbon black, may be present in an amount of 80% by weight or less, 60% by weight or less, 50% by weight or less, 40% by weight or less, 30% by weight or less, for example, about 15% by weight to about 80% by weight, about 20% by weight to about 80% by weight, about 25% by weight to about 80% by weight, about 30% by weight to about 80% by weight, about 35% by weight to about 80% by weight, about 40% by weight to about 80% by weight, about 15% by weight to about 70% by weight, about 20% by weight to about 70% by weight, about 25% by weight to about 70% by weight, about 30% by weight to about 70% by weight, The liquid content (e.g., water content) can be about 35% to about 80% by weight, about 40% to 70% by weight, about 15% to about 65% by weight, about 20% to about 65% by weight, about 25% to about 65% by weight, about 30% to about 65% by weight, about 35% to about 65% by weight, about 40% to about 65% by weight, about 15% to about 60% by weight, about 20% to about 60% by weight, about 25% to about 60% by weight, about 30% to about 60% by weight, about 35% to about 60% by weight, or about 40% to about 60% by weight, or any other range from these various values given herein. The wet filler can have a liquid content of at least 30% by weight (based on the weight of the filler), or at least 40% by weight, or in an amount of 20% to 80% by weight.
[0060] As disclosed herein, the first and second fillers can be independently selected to be the same or different. The filler, whether the first and / or second filler, can be chemically treated (e.g., chemically treated carbon black, chemically treated silica, silicon treated carbon black) and / or chemically modified. The filler can be or include carbon black with an organic group attached. The filler can have one or more coatings present on the filler (e.g., silicon coated material, silica coated material, carbon coated material). The filler can be oxidized and / or have other surface treatments.
[0061] The first and second fillers can be independently selected from particulate, or fibrous, or platelet-like fillers. For example, particulate fillers are made of discrete agglomerates. Such fillers can often have an aspect ratio (e.g., length to diameter) of 3:1 or less, or 2:1 or less, or 1.5:1 or less. Fibrous fillers can have an aspect ratio of, for example, 2:1 or more, 3:1 or more, 4:1 or more, or more. Typically, fillers used to reinforce elastomers have dimensions that are microscopic (e.g., hundreds of microns or less) or nanoscale (e.g., less than 1 micron). In the case of carbon black, the discrete agglomerates of particulate carbon black are described as aggregates or agglomerates formed from primary particles, and not the primary particles themselves. In other embodiments, the fillers can have a platelet-like structure, such as graphene and reduced graphene oxide.
[0062] The first and second fillers may be independently selected from the group consisting of carbonaceous materials, carbon black, silica, nanocellulose, lignin, clay, nanoclay, metal oxides, metal carbonates, pyrolytic carbon, regenerated carbon, regenerated carbon black (e.g., as defined by ASTM D8178-19, rCB, graphene, graphene oxide, reduced graphene oxide (e.g., reduced graphene oxide worms as disclosed in PCT Publication WO2019 / 070514A1, or densified reduced graphene oxide granules as disclosed in U.S. Provisional Application No. 62 / 857,296, filed June 5, 2019, and PCT Publication No. 2020 / 247681, the disclosures of which are incorporated herein by reference), carbon nanotubes, single-walled carbon nanotubes, multi-walled carbon nanotubes, combinations thereof, and coated and treated materials thereof. Other suitable fillers include carbon nanostructures (CNS, single CNS), e.g., multiple carbon nanotubes in the form of dendrimers that are combined, entangled, and / or cross-linked in a polymeric structure by sharing a common layer with each other and being branched. and carbon nanotubes (CNTs). CNS fillers are described in U.S. Pat. No. 9,447,259 and PCT Application PCT / US2021 / 027814, the disclosures of which are incorporated herein by reference. The filler can be chemically treated (e.g., chemically treated carbon black, chemically treated silica, silicon treated carbon black) and / or chemically modified. The filler can be, or can include, carbon black having organic groups attached thereto. The filler can have one or more coatings present on the filler (e.g., silicon coated material, silica coated material, carbon coated material). The filler can be oxidized and / or other surface treated. There is no limitation as to the type of filler (e.g., silica, carbon black, or other filler) that can be used.
[0063] As previously mentioned, fibrous fillers can also be incorporated as first and / or second fillers in the methods disclosed herein, including natural, semi-synthetic, and / or synthetic fibers (e.g., nano-sized carbon fibers), such as the short fibers disclosed in PCT Publication WO2021 / 153643, the disclosure of which is incorporated herein by reference. Other fibrous fillers include poly(p-phenylene terephthalamide) pulp, commercially available as Kevlar® pulp (Du Pont).
[0064] Other suitable fillers include bio-based or bio-based materials (derived from biological sources), recycled materials, or other fillers considered renewable or sustainable, including hydrothermal carbon (HTC, which includes lignin treated by hydrothermal carbonization as described in U.S. Patent Nos. 10,035,957 and 10,428,218, the disclosures of which are incorporated herein by reference), rice husk silica, carbon from methane pyrolysis, engineered polysaccharide particles, starch, siliceous earth, ground rubber, and functionalized ground rubber. Exemplary engineered polysaccharides include those described in U.S. Patent Application Publication Nos. 2020 / 0181370 and 2020 / 0190270, the disclosures of which are incorporated herein by reference. For example, the polysaccharide can be selected from poly alpha-1,3-glucan; poly alpha-1,3-1,6-glucan; water-insoluble alpha-(1,3-glucan) polymers having 90% or more alpha-1,3-glycosidic linkages, less than 1% by weight alpha-1,3,6-glycosidic branch points, and a number average degree of polymerization in the range of 55 to 10,000; dextran; compositions comprising poly alpha-1,3-glucan ester compounds; and water-insoluble celluloses having a weight average degree of polymerization (DPw) of about 10 to about 1,000 and a cellulose II crystal structure.
[0065] The carbon black can be untreated or treated carbon black or a mixture thereof. The filler can be or include pellets, fluffy powder, granules, and / or agglomerates. The wet carbon black can be formed into pellets, granules, or agglomerates, for example, in a pelletizer, fluidized bed, or other equipment that creates a wet filler.
[0066] The wet carbon black can be one or more of the following: Undried carbon black, and / or Undried carbon black pellets, and / or dried carbon black that has been rewetted in a pelletizer, for example with water, and / or Dry carbon black that has been ground and rewetted with water in a pelletizer, and / or Dry carbon black mixed with water, and / or Fluffy powder, granules, or agglomerates mixed with water.
[0067] In a typical carbon black manufacture, carbon black is initially prepared as a dry, finely particulate (fluffy) material. This fluffy carbon black can be densified by a conventional pelletizing process, for example, by mixing the carbon black with a liquid, such as adding water, and feeding the mixture to a pin pelletizer. Pin pelletizers are well known in the art and include the pin pelletizer described in U.S. Pat. No. 3,528,785. The resulting wet pellets are then heated under controlled temperature and time parameters to remove the liquid from the pellets prior to further handling and shipping. In other processes, carbon black pellets can be produced by a process that omits the drying step. In such processes, the pelletized carbon black contains at least 20% by weight, such as at least 30% by weight, or at least 40% by weight, of process water, based on the total weight of the wet carbon black.
[0068] Alternatively, dried carbon black pellets (e.g., commercially available carbon black pellets) can be rewetted in a pelletizer. The pellets can be granulated, crushed, classified, and / or milled, for example, in a jet mill. The resulting carbon black is in a fluffy form and can be repelletized in a pelletizer or can be otherwise compressed or agglomerated in the presence of water to wet the carbon black. Alternatively, the fluffy carbon black can be compressed into other shapes, for example, in the shape of a square block, in equipment known in the art. Alternatively, the carbon black, for example, carbon black pellets or fluffy carbon black, can be wetted, for example, by using a fluidized bed, a sprayer, a mixer, or a rotating drum. When the liquid is water, the undried or rewetted carbon black can have a water content ranging from 20% to 80%, 30% to 70%, or other ranges, for example, 55% to 60%, by weight, based on the total weight of the wet carbon black.
[0069] The carbon black used in any of the methods disclosed herein, whether it is a first filler and / or a second filler, may be a reinforcing carbon black, a semi-reinforcing carbon black, or a non-reinforcing carbon black, e.g., 20m 2 / g~250m 2 Other carbon blacks may be used having a statistical thickness surface area (STSA) in the range of 100 / g or more. STSA (statistical thickness surface area) is measured based on ASTM test procedure D-5816 (measured by nitrogen adsorption). Examples of reinforcing grades of the ASTM grade include N110, N121, N134, N220, N231, N234, N299, N326, N330, N339, N347, N351, N358, and N375 carbon black. Examples of semi-reinforcing grades of the ASTM grade include N539, N550, N650, N660, N683, N762, N765, N774, N787, N990 carbon black, and / or N990 grade thermal black.
[0070] As mentioned above, the carbon black can be rubber black, for example, reinforcing grade carbon black or semi-reinforcing grade carbon black. Carbon blacks sold under the trademarks Regal®, Black Pearls®, Spheron®, Sterling®, Propel®, Endure®, and Vulcan® available from Cabot Corporation, Raven®, Statex®, Furnex®, and Neotex®, as well as CD and HV series available from Birla Carbon (previously available from Columbian Chemicals), and Corax®, Durax®, Ecorax®, and Purex® CK series available from Orion Engineered Carbons (previously available from Evonik and Degussa Industries), as well as other suitable fillers used in rubber or tire applications can also be utilized for use with various implementations. Suitable chemically functionalized carbon blacks include those disclosed in International Publication WO 96 / 18688 and U.S. Patent Application Publication No. 2013 / 0165560, the disclosures of which are incorporated herein by reference. Mixtures of any of these carbon blacks can be used.
[0071] The carbon black can be an oxidized carbon black, such as a carbon black that has been surface treated with an oxidizing agent. Additionally, carbon blacks prepared using other surface modification methods that introduce ionic or ionizable groups onto the pigment surface can also be used. Processes that can be used to produce oxidized carbon blacks are known in the art, and several types of oxidized carbon blacks are commercially available.
[0072] The carbon black can be furnace black, gas black, thermal black, acetylene black, or lamp black, plasma black, recycled carbon black (e.g., as defined in ASTM D8178-19) or carbon products containing silicon-containing and / or metal-containing species. The carbon black can be a multiphase aggregate containing at least one carbon phase and at least one phase of metal-containing species or silicon-containing species, i.e., silicon-treated carbon black. In silicon-treated carbon black, the silicon-containing species is distributed as an inherent part of the carbon black, for example as an oxide or carbide of silicon, throughout at least a portion of the carbon black. Silicon-treated carbon black actually represents a two-phase aggregate particle, rather than a coated or otherwise modified carbon black aggregate. One phase is carbon, which is still present as black smoke crystals and / or amorphous carbon, while the second phase is silica and / or other silicon-containing species). Thus, the silicon-containing species phase of the silicon-treated carbon black is an inherent part of the aggregate and is distributed throughout at least a portion of the aggregate. Ecoblack™ silicon-treated carbon black is available from Cabot Corporation. The preparation and properties of these silicon-treated carbon blacks are described in U.S. Patent No. 6,028,137, the disclosure of which is incorporated herein by reference.
[0073] Alternatively, the filler, for example carbon black, whether it is the first and / or second filler, can be chemically treated. For example, the carbon black can have at least one organic group attached thereto. The attachment can occur by diazonium reaction, and at least one organic group has a diazonium salt, as detailed in, for example, U.S. Patent Nos. 5,554,739, 5,630,868, 5,672,198, 5,707,432, 5,851,280, 5,885,335, 5,895,522, 5,900,029, and 5,922,118, the disclosures of which are incorporated herein by reference.
[0074] With regard to the filler, whether it is the first and / or second filler, one option is at least silica, one or more types of silica, or any combination of silica, which may be used in any embodiment disclosed herein. The silica may include precipitated silica, fumed silica, silica gel, and / or colloidal silica, or may be. The silica may be untreated silica and / or chemically treated silica, or may be. The silica may be suitable for reinforcing elastomer composites and may be present in an amount of about 20 m. 2 / g ~ approx. 450m 2The silica is characterized by a Brunauer-Emmett-Teller surface area (BET, multipoint BET nitrogen adsorption, ASTM D1993) of 100 / g. Highly dispersible precipitated silica ("HDS") is understood to mean any silica that does not agglomerate and has a substantial ability to disperse in an elastomeric matrix. Verification of such dispersion can be observed by electron or optical microscopy on thin sections of the elastomeric composite in a known manner. Examples of commercial varieties of HDS include Perkasil® GT 3000GRAN silica from WR Grace & Co, Ultrasil® 7000 silica from Evonik Industries, Zeosil® 1165 MP, 1115 MP, Premium, and 1200 MP silica from Solvay SA, Hi-Sil® EZ 160G silica from PPG Industries, Inc., and Zeopol® 8741 or 8745 silica from Evonik Industries. Conventional non-HDS precipitated silicas can also be used. Examples of commercial grades of conventional precipitated silicas include Perkasil® KS 408 silica from WR Grace & Co, Zeosil® 175GR silica from Solvay SA, Ultrasil® VN3 silica from Evonik Industries, and Hi-Sil® 243 silica from PPG Industries, Inc. Precipitated silicas with silane coupling agents bonded to their surfaces can also be used. Examples of commercial grades of chemically treated precipitated silicas include Agilon® 400, 454, or 458 silica from PPG Industries, Inc., and Coupsil silicas, such as Coupsil® 6109 silica from Evonik Industries.The intermediate form of silica in the form of a cake or paste obtained from the precipitation process, which has not been dried (undried silica), can be added directly to the mixer as a wet filler, thus eliminating the complex drying and other downstream processing steps used in the conventional manufacture of precipitated silica.
[0075] In any embodiment and at any step, the coupling agent can be introduced at any step (or steps or locations) so long as the coupling agent has an opportunity to become dispersed in the composite (e.g., the method further includes the step of charging the mixer with the coupling agent). The coupling agent can be or include one or more silane coupling agents, one or more zirconate coupling agents, one or more titanates, one or more nitro coupling agents, or any combination thereof. Coupling agents include bis(3-triethoxysilylpropyl)tetrasulfane (e.g., Si 69 from Evonik Industries, Struktol SCA98 from Struktol Company), bis(3-triethoxysilylpropyl)disulfane (e.g., Si 75 and Si 266 from Evonik Industries, Struktol SCA985 from Struktol Company), 3-thiocyanatopropyltriethoxysilane (e.g., Si 264 from Evonik Industries), gamma-mercaptopropyl-trimethoxysilane (e.g., VP Si 163 from Evonik Industries, Struktol SCA989 from Struktol Company), gamma-mercaptopropyl-triethoxysilane (e.g., VP Si 163 from Evonik Industries, Struktol SCA989 from Struktol Company), 3-thiocyanatopropyl ... 263), zirconium dineoalkanolatodi(3-mercapto)propionato-O,N,N'-bis(2-methyl-2-nitropropyl)-1,6-diaminohexane, S-(3-(triethoxysilyl)propyl)octanethioate (e.g., NXT coupling agent from Momentive (Friendly, WV)), and / or commercially similar or coupling agents having one or more of the same chemical groups. Further specific examples of coupling agents include, by trade name, but are not limited to, VP Si 363 from Evonik Industries, and NXT Z and NXT Z-50 silanes from Momentive.Other compounds that can function as coupling agents include those compounds having a nitroxide radical, such as TEMPO (2,2,6,6-tetramethyl-1-piperidinyloxy radical), as disclosed in U.S. Pat. Nos. 6,084,015, 6,194,509, 8,584,725, and U.S. Patent Application Publication No. 2009 / 0292044, the disclosures of which are incorporated herein by reference, or the nitrile oxides, nitrile imines, and nitrone 1,3-dipole compounds disclosed in U.S. Pat. Nos. 10,239,971, 10,202,471, 10,787,471, and U.S. Patent Application Publication No. 2020 / 0362139, the disclosures of which are incorporated herein by reference. The coupling agents disclosed herein can be used to provide a hydrophobic surface modification of the silica (pre-coupled or pre-treated silica) prior to using it in any of the processes disclosed herein. It should be understood that any combination of elastomer, additives, and further composite materials can be added to the elastomer composite, for example in a compounder.
[0076] Alternatively, the mixing step can be carried out without a coupling agent (eg, the filler comprises silica and / or silicon treated carbon black).
[0077] Other fillers are disclosed in U.S. Patent Application Publication No. 2018 / 0282523 and European Patent No. 2423253 B1, the disclosures of which are hereby incorporated by reference.
[0078] Particular types of internal mixers include Banbury mixers or Brabender mixers, either of which may be used in the methods of forming composites described herein. The internal mixer may be a tangential internal mixer. The internal mixer may be an intermeshing internal mixer. Other mixers include kneading type internal mixers. Commercially available internal mixers from Farrel-Pomini, Harburg Freudenberger Maschinenbau GmbH (HF), Kobelco, or Pelmar Eng'r Ltd may be used. Examples of mixers and designs that may be used are described in EP 2423253 B1 and U.S. Pat. No. 7,556,419, the disclosures of which are incorporated herein by reference. Alternatively, the mixer may be a continuous mixer. For example, the liquid masterbatch and wet filler can be mechanically processed using one or more of a continuous internal mixer, twin screw extruder, single screw extruder, or roll mill, such as those described in U.S. Patent No. 9,855,686 B2, the disclosure of which is incorporated herein by reference. Suitable kneading and mastication equipment is well known and commercially available, such as the Unimix Continuous Mixer and MVX (mixing, degassing, extrusion) Machine from Farrel Pomini Corporation (Ansonia, Connecticut), the FCM™ Farrel Continuous Mixer from Pomini, Inc., long shaft continuous mixers, Pomini continuous mixers, twin rotor co-rotating intermeshing extruders, twin rotor counter-rotating non-intermeshing extruders, Banbury mixers, Brabender mixers, intermeshing internal mixers, kneading internal mixers, continuous compounding extruders, Kobe Steel, Ltd. twin screw kneading extruders, and Kobe continuous mixers. Alternative mastication equipment suitable for use in various aspects of the present invention will be familiar to those skilled in the art.
[0079] The discharged composite can be subjected to one or more post-processing steps. Post-processing can occur after any mixing step. In multi-stage mixing, post-processing can be performed after the first stage and / or the second stage, etc. The composite can be post-processed to provide a composite that is dried, homogenized, extruded, calendared, kneaded, etc. The one or more post-processing steps can mold or form or allow for improved handling, but preferably do not substantially disperse the filler.
[0080] In any of the methods for making the composite material disclosed herein, the method may further comprise, after formation of the composite material, one or more of the following steps: one or more holding steps, One or more drying steps can be used to further dry the composite to obtain a dry composite; one or more extrusion processes, one or more calendering steps, one or more milling steps to obtain a milled composite material, one or more granulation steps, one or more cutting steps, one or more baling steps to obtain a baled product or mixture, one or more bale mixtures or products are broken down to form a granulated mixture; and / or one or more mixing or blending steps, and / or One or more sheeting processes.
[0081] As a further example, the following sequence of steps may occur, and each step may be repeated any number of times (with the same or different settings) after formation of the composite. one or more holding steps to further improve elasticity, one or more cooling steps, drying the composite to obtain a further dried composite, mixing or blending the composite materials to obtain a blended mixture, milling the blended mixture to obtain a milled mixture; Granulation of the milled mixture; Optionally, baling the mixture after granulation to obtain a baled mixture. Optionally, breaking down and mixing the baled mixture.
[0082] Additionally or alternatively, the composite can be compounded with one or more of antidegradants, rubber chemicals, and / or curatives and vulcanized to form a vulcanizate. Such vulcanized compounds can have one or more improved properties, such as one or more improved rubber properties, such as, but not limited to, improved hysteresis, abrasion resistance, and / or rolling resistance, e.g., in tires, or improved mechanical and / or tensile strength, or improved tan delta and / or improved tensile stress ratio.
[0083] Rubber chemicals as defined herein include one or more processing aids (e.g., various oils and plasticizers, waxes, to facilitate mixing and processing of the rubber), activators (e.g., zinc oxide and fatty acids, to activate the vulcanization process), accelerators (e.g., sulfenamides and thiazoles, to accelerate the vulcanization process), vulcanizing agents (or curatives, e.g., sulfur, peroxides, to crosslink the rubber), and other rubber additives, including, but not limited to, retarders, crosslinking aids, peptizers, adhesion promoters (e.g., the use of cobalt salts to promote adhesion of steel cords to rubber-based elastomers (e.g., as described in U.S. Pat. No. 5,221,559 and U.S. Patent Application Publication No. 2020 / 0361242, the disclosures of which are incorporated herein by reference), resins (e.g., tackifiers, traction promoting resins, flame retardants, colorants, blowing agents, and exothermic agents). Additives for reducing hygroscopic adhesion (HBU), and crosslinking agents, such as those described in U.S. Provisional Patent Application No. 63 / 123,386, the disclosure of which is incorporated herein by reference. In one alternative, the rubber chemicals can include processing aids and activators. In another alternative, the one or more rubber chemicals can be selected from zinc oxide, fatty acids, zinc salts of fatty acids, waxes, accelerators, resins, and process oils. Exemplary resins include one or more C5 resins, C5-C9 resins, C9 resins, rosin resins, terpene resins, aromatic modified terpene resins, dicyclopentadiene resins, alkylphenol resins, and those resins disclosed in U.S. Pat. Nos. 10,738,178, 10,745,545, and U.S. Patent Publication No. 2015 / 0283854, the disclosures of which are incorporated herein by reference.
[0084] As an example, in a compounding step, the components of the curative package are mixed with the neat composite in a mixing device, except for the sulfur or other crosslinking agents and accelerators (non-vulcanizing agents, such as rubber chemicals and / or antidegradants, are often premixed and are collectively referred to as "smalls"). The most common mixing device is an internal mixer, such as a Banbury or Brabender mixer, however other mixers, such as continuous mixers (e.g., extruders), can also be used. Thereafter, in a later or second compounding step, the crosslinking agent, such as sulfur, and accelerators (if required) (collectively referred to as vulcanizing agents) are added. The compounding step is often carried out in the same type of equipment as the mixing step, however, it can be carried out in a different type of mixer or extruder or roll mill. Those skilled in the art will understand that once the vulcanizing agents are added, vulcanization will begin once the proper activation conditions for the crosslinking agents are reached. Thus, when sulfur is used, the temperature during mixing is preferably kept substantially below the vulcanization temperature.
[0085] Also disclosed herein is a method of making a vulcanizate, the method including at least the step of curing the composite in the presence of at least one curative, the curing being accomplished by application of heat, pressure, or both, as is known in the art.
[0086] Also disclosed herein are articles made from or including the composites or vulcanizates disclosed herein.
[0087] The composites can be used to make elastomer or rubber-containing products. As an option, the elastomer composites can be used or manufactured for use in forming vulcanizates that are incorporated into various tire components, such as tire treads (e.g., on-road or off-road tire treads), caps and bases, undertreads, innerliners, tire sidewalls, tire carcasses, tire sidewall inserts, tire wire skim, and mountain tire cushion gums, in pneumatic and non-pneumatic or solid tires. Alternatively, or in addition, the elastomer composites (and the subsequent vulcanizates) can be used in hoses, seals, gaskets, weatherstripping, windshield wipers, automotive parts, liners, pads, housings, wheel and truck elements, tire sidewall inserts, tire wire skim, and mountain tire cushion gums, in pneumatic and non-pneumatic or solid tires. Alternatively, or in addition, the elastomeric composites (and subsequent vulcanizates) can be used in a variety of applications, such as hoses, seals, gaskets, vibration isolation articles, trucks, tracked propulsion systems, such as track pads for bulldozers, engine mounts, earthquake resistance, mining equipment, such as screens, linings for mining equipment, conveyor belts, chute liners, slurry pump liners, mud pump parts, such as impellers, valve seats, valve bodies, piston hubs, piston rods, plungers, and a variety of applications, such as mixing slurries and slurry pump inlets. The compositions may be used in impellers for impellers, grinding mill liners, cyclones and hydrocyclones, expansion joints, marine equipment such as linings for pumps (e.g., dredge pumps and outboard motor pumps), hoses (e.g., dredge hoses and outboard motor hoses) and other marine equipment, shaft seals for marine, oil, aerospace and other applications, propeller shafts, linings for transport pipes such as oil sands and / or tar sands, and other applications where wear resistance and / or improved dynamic properties are required.Additionally, the elastomeric composites, via the vulcanized elastomeric composites, can be used in rollers, cams, shafts, pipes, vehicle bushings, or other applications where wear resistance and / or improved dynamic properties are required.
[0088] Thus, the articles include vehicle tire treads, such as caps and bases, sidewalls, undertreads, innerliners, wire skims, tire carcasses, engine mounts, bushings, conveyor belts, vibration isolators, weatherstripping, windshield wipers, automotive parts, seal gaskets, hoses, liners, pads, housings, and wheel and track elements. For example, the article can be a multi-component tread, such as those disclosed in U.S. Patent Nos. 9,713,541, 9,713,542, 9,718,313, and 10,308,073, the disclosures of which are incorporated herein by reference. EXAMPLES
[0089] Example A: Preparation of liquid masterbatch This example describes the preparation of a liquid masterbatch from a carbon black slurry and a latex.
[0090] Preparation of carbon black slurry Dry carbon black (N134) (Cabot Corporation, Boston, Massachusetts) was mixed with water and milled to form a slurry having a consistency of about 13.5%. The slurry was fed to the mixing zone of the coagulation reactor shown in Figures 2-4 and 7 of U.S. Pat. No. 6,929,783 by a homogenizer equipped with a flat-seat homogenizing valve (APV Homogenizer Division, APV Gaulin, Inc., Wilmington, Massachusetts) at an operating pressure of about 3000 psig, whereby the slurry was introduced as a jet of finely dispersed carbon black slurry into the mixing zone of the coagulation reactor. The flow rate of the carbon black slurry was adjusted from about 1200 to 2500 kg / hr to modify the final carbon black loading (phr) and obtain the desired production rate. The actual carbon black loading was determined by nitrogen pyrolysis and thermogravimetric analysis (TGA). Specific carbon black grades and loadings are given in the table below.
[0091] Supply of natural rubber latex Field latex (diluted and desludged field latex) having a dry rubber content of about 27-31% was pumped to the mixing section of a coagulation reactor configured as shown in Figures 2-4 and 7 of U.S. Patent No. 6,929,783. The latex flow rate was adjusted to modify the final carbon black loading in the range of about 1000-2500 kg / hr.
[0092] Liquid Masterbatch Production The carbon black slurry and latex were mixed in the mixing zone of the coagulation reactor by entraining the latex stream with the carbon black slurry stream. During the entrainment process, the carbon black was intimately mixed into the latex and the mixture was coagulated.
[0093] The masterbatch crumb was discharged from the coagulation reactor at rates ranging from 500 to 1000 kg / hr (dry weight) and dewatered to about 10 to 20% moisture in a dewatering extruder (The French Oil Machinery Company, Piqua, Ohio) as shown in Figures 1, 8, and 9 of U.S. Pat. No. 6,929,783 and described herein.
[0094] The dewatered coagulum was dumped into a continuous compounder (Farrel Unimix Continuous Mixer (FCM), equipped with two #15 rotors and operating at 190-320 rpm, Farrel Corporation, Ansonia, CT) where the dewatered coagulum was masticated and mixed with 1-2 phr of antioxidant (6PPD) as described in U.S. Pat. No. 8,586,651. The moisture content of the masticated masterbatch exiting the FCM was approximately 1-2% and the temperature ranged from 140-180°C. The product was further masticated, cooled, and dried on an open mill. The product was further cooled in a cooling conveyor and cut into small strips which were pressed together to form a "loose" product bale of liquid masterbatch. The resulting masterbatch was used in compounding the rubber compounds shown in the table below.
[0095] Example B: Preparation of composites, vulcanizates from liquid masterbatches and comparative examples For the composites prepared according to the claimed invention, i.e. (samples with wet carbon black, Examples 1, 3, 5, 7 and 8, and samples with wet silica, Examples 9, 10 and 11), wet carbon black and wet silica were obtained by rewetting the dry materials with water in a pin pelletizer. The water content is disclosed in Tables 4-7 below.
[0096] Mixing and blending were performed in a BR-1600 Banbury® laboratory mixer ("BR1600" mixer, Farrel Corporation, Ansonia, Conn.). The BR1600 mixer was operated with a 2-blade tangential rotor (2WL) giving a capacity of 1.6 L, and all mixing and blending was performed at a mixer speed of 70 rpm, ram pressure of 2.8 bar unless otherwise noted. The times given in Tables 2, 3 and 4 are the mixing process times for each step.
[0097] The natural rubber used was standard grade SMR20 (Hokson Rubber, Malaysia). Technical descriptions of this natural rubber are widely available, for example Rubber World Magazine's Blue Book, published by Lippincott and Peto, Inc. (Akron, Ohio, USA). The butadiene rubber (BR) used was Buna® CB 22 from Arlanxeo (Canada) and the styrene butadiene rubber (SBR) used was Kralex SBR 1500 from Synthos Rubbers (Czech Republic).
[0098] vulcanizate Bales of liquid masterbatch were compounded according to the formulations in Table 1 and the process outlined in Table 2 (both wet and dry filler comparative examples). The TCU temperatures of samples 1, 5, 7 and 9 were 90° C., while the remaining samples had a TCU temperature of 60° C. The amounts of masterbatch and unfilled rubber were selected such that the final rubber compound contained 50 phr of filler unless otherwise noted. [Table 1] a. Wet N134 carbon black (samples 1, 3, 5, and 7) or wet N234 carbon black (sample 8) obtained from Cabot Corporation, or wetted Zeosil™ Z1165 MP silica (samples 9, 10, and 11) obtained from Solvay USA Inc. (Cranbury, NJ). b. The composition and mixing conditions of the second masterbatch are given in Table 4. c. Poly(ethylene glycol), PEG 3500, obtained from Akrochem, was added to formulations containing silica as an additional filler. dN-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine eN-Cyclohexyl-2-benzothiazole sulfonamide [Table 2]
[0099] After dumping, the composites were sheeted on a two-roll mill operated at about 37 rpm at 50°C, followed by three or five passes with a nip separation of about 5 mm and a rest period of at least 3 hours before the next stage of mixing. Curatives were added in the final (productive) mix stage as listed in Table 3. All formulations were cured at 150°C for a time determined by (1.1 x t90). [Table 3]
[0100] Table 4 gives the specific procedures for example and comparative second masterbatch samples MB3, MB8, MB C3, and MB C8. [Table 4]
[0101] Tables 6 and 7 list the type of carbon black or silica filler, filler loading, mixing procedure, operating conditions, and the resulting data for each sample. Mooney viscosity was measured at 100°C according to ASTM D1646. Tensile stress at 100% elongation (M100) and 300% elongation (M300) were evaluated according to ASTM D412 (Test Method A, Die C) at 50% relative humidity and 500 mm / min crosshead speed. An extensometer was used to measure the tensile strain. The ratio of M300 / M100 is expressed as the modulus ratio. The maximum tan δ was measured on an ARES G2 rheometer (manufacturer: TA Instruments) in torsion mode. The diameter size of the vulcanizate specimens was 8 mm in diameter and approximately 2 mm thick. The rheometer was operated at a constant temperature of 60°C and a constant frequency of 10 Hz. Strain sweeps were performed from 0.1 to 68% strain. Measurements were made at 10 points per set and the maximum tan δ measured was reported. Macrodispersion was measured according to the procedure of ASTM D7723-11. Three images were taken for each sample tested and the average result was determined. The minimum cut-off diameter was 5 μm. The value defined as "white area" in the ASTM standard method is reported here as the undispersed area. [Table 5] [Table 6] [Table 7]
[0102] As can be seen from Tables 5-7, the addition of a liquid masterbatch of the filler in wet form, and optionally a second elastomer, according to the process of the present invention produced rubber compounds with better dispersion of the filler in the rubber and better overall rubber properties, e.g., higher M300, modulus ratio and / or lower tan δ value, than observed for the comparative rubber compounds prepared by the addition of a liquid masterbatch of the filler in dry form. In the case of a liquid masterbatch containing natural rubber, the compounding of the wet filler of the rubber compound with the liquid masterbatch can be carried out under more intense mixing conditions, without rubber degradation, to obtain a dispersion level with better rubber reinforcing properties. The rubber compositions of the present invention were characterized by enhanced filler dispersion. The intermediate composite properties, e.g., Mooney viscosity, indicate the suitability of the present invention for use in conventional rubber compounding processes, e.g., in compounding rubber compounds for the manufacture of tires and industrial rubber articles. Moreover, the results were obtained other than in conventional rubber mixing equipment using the selected combination of process conditions according to the present invention.
[0103] Use of the terms "a" and "an" and "the" should be understood to encompass both the singular and the plural unless otherwise indicated or clearly contradicted by context. The terms "comprising," "having," "including," and "containing" should be understood to be open ended (i.e., meaning "including, but not limited to") unless otherwise indicated. The recitation of ranges of values herein is merely intended to serve as a shorthand method of independently expressing each individual value falling within the range, unless otherwise indicated herein, and each individual value is incorporated into the specification as if it were independently set forth herein. All methods described herein can be performed in any suitable order unless otherwise indicated herein or otherwise clearly contradicted by context. The use of any and all examples or exemplary terms provided herein (e.g., "for example") are merely intended to better clarify the invention and do not pose a limitation on the scope of the invention unless otherwise indicated. No language in the specification should be construed as indicating any non-claimed element essential to the practice of the invention.
Claims
1. A method for preparing a composite material, comprising the steps of: (a) charging a mixer having one or more rotors with (i) a liquid masterbatch comprising a first filler dispersed in at least one elastomer, and (ii) a wet filler comprising a second filler and a liquid present in an amount ranging from 15% to 65% by weight based on the total weight of the wet filler, wherein the liquid masterbatch represents a masterbatch derived from an elastomer latex or polymer solution and a filler slurry, and wherein the first and second fillers are selected from the group consisting of carbonaceous material, carbon black, silica, nanocellulose, lysine, cellulose, cellulose acetate, cellulose ether ... the liquid masterbatch comprises at least one material selected from cellulose, clay, nanoclay, metal oxides, metal carbonates, pyrolytic carbon, regenerated carbon, graphene, graphene oxide, reduced graphene oxide, carbon nanotubes, combinations thereof, and coated and treated materials thereof, the liquid is a volatile liquid having a boiling point between 60°C and 180°C, and the wetting filler is in the form of a powder, paste, pellets, or cake, the first filler dispersed in the liquid masterbatch can be the same or different from the second filler of the wetting filler, (b) mixing said liquid masterbatch with said wet filler in one or more mixing steps to form a mixture, wherein in at least one of said mixing steps, said mixing is performed with a mixer temperature controlled by at least one temperature control means, and removing at least a portion of said liquid from said mixture by evaporation; and (c) discharging from the mixer the composite comprising the first and second fillers dispersed in the at least one elastomer at a total loading of at least 20 phr, the composite having a liquid content of 10% by weight or less, based on the total weight of the composite; The method comprising:
2. 2. The method of claim 1, wherein in step (b) and optionally in step (a), the at least one temperature control means is set to a temperature control unit temperature of 65° C. or greater.
3. 2. The method of claim 1, wherein in step (b) and optionally in step (a), the at least one temperature control means is set to a temperature control unit temperature in the range of 65°C to 100°C.
4. 4. The method of any one of claims 1 to 3, wherein one or more rubber chemicals are not present in the composite discharged in step (c), said rubber chemicals being selected from the group consisting of processing aids, activators, zinc oxide, fatty acids, zinc salts of fatty acids, waxes, accelerators, resins and processing oils.
5. The method of any one of claims 1 to 4, wherein the wetting filler comprises a liquid present in an amount in the range of 30% to 65% by weight.
6. 6. The method of any one of claims 1 to 5, wherein the at least one elastomer is selected from natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, functionalized polybutadiene rubber, polyisoprene rubber, ethylene-propylene rubber, isobutylene based elastomers, polychloroprene rubber, nitrile rubber, hydrogenated nitrile rubber, polysulfide rubber, polyacrylate elastomers, fluoroelastomers, perfluoroelastomers, silicone elastomers, and mixtures thereof.
7. The method of any one of claims 1 to 6, wherein the step of charging comprises charging the mixer with at least one additional elastomer.
8. The method of claim 7 , wherein the at least one additional elastomer is different from the at least one elastomer of the liquid masterbatch and forms a composite with an elastomer mixture.
9. 9. The method of claim 8, wherein the at least one elastomer of the liquid masterbatch is natural rubber and the at least one additional elastomer is selected from polybutadiene rubber and styrene-butadiene rubber.
10. The method of any one of claims 1 to 9, wherein the first and second fillers comprise at least one material selected from carbon black, silica, and silicon-treated carbon black.
11. The method of any one of claims 1 to 9, wherein the first and second fillers comprise carbon black.
12. The method of any one of claims 1 to 9, wherein the wet filler comprises undried carbon black.
13. The method of any one of claims 1 to 9, wherein the wet filler comprises dry re-wetted carbon black.
14. The method of any one of claims 1 to 9, wherein the first and second fillers comprise silica.
15. The method of any one of claims 1 to 9, wherein the wet filler comprises silica that has not been dried.
16. The method of any one of claims 1 to 9, wherein the wet filler comprises rewetted dried silica.
17. The method of any one of claims 14 to 16, further comprising charging the mixer with a coupling agent.
18. 1. A method for preparing a vulcanizate comprising the steps of: A method comprising curing the composite prepared by the method of any one of claims 1 to 17 in the presence of at least one curative to form the vulcanizate.
Citation Information
Patent Citations
Rubber composition and production method thereof
JP2013199543A
Elastomer composite blend, method and apparatus for producing the same.
JP2013505325A
Manufacturing method of wet master batch
JP2017088747A
Method for producing silica and carbon black reinforced elastomeric composites and products containing same
JP2018524450A
Method for preparing a composite comprising an elastomer, a filler and a crosslinker
JP2023554609A